Antibacterial and anti-quorum sensing activities of a substituted thiazole derivative against methicillin-resistant Staphylococcus aureus and other multidrug-resistant bacteria. (December 2020) - Ibrahim, Yasser Musa; Abouwarda, Ahmed Megahed; Nasr, Tamer; Omar, Farghaly Abdelhamid; Bondock, Samir
Abstract: Management of infections caused by methicillin-resistant Staphylococcus aureus (MRSA) is still challenging. We herein report the antibacterial and anti-quorum sensing (anti-QS) activities of 5-acetyl-4-methyl-2-(3-pyridyl) thiazole (AMPT) against MRSA and other multidrug-resistant bacteria. Minimum inhibitory concentrations (MICs) were determined by agar dilution method and bactericidal activity was assessed by a time-kill assay. The anti-QS activity was evaluated using Chromobacterium violaceum . The effect of AMPT on virulence factors production by MRSA and biofilm formation by MRSA, C. violaceum and Pseudomonas aeruginosa was also assessed. AMPT was superior to vancomycin and teichoplanin against MRSA isolates. MIC50/90 values of AMPT (2/4 mg/L) were 2–4 folds lower than the values for vancomycin (4/16 mg/L) and 2-fold lower than the values for teichoplanin (4/8 mg/L). Results of time-kill assay against two multidrug-resistant MRSA isolates revealed bactericidal effect of AMPT after 4 h of treatment, with no bacterial cells detected after 24 h. Remarkably, AMPT exhibited anti-QS activity against both C. violaceum and MRSA at subinhibitory concentrations. Moreover, AMPT reduced haemolysin and protease production by MRSA and inhibited biofilm formation by MRSA, C. violaceum and P. aeruginosa but had no dispersion effect on preformed ones. Furthermore, molecular docking analysis revealed promising interactions between AMPT and AgrA as well as SarA in S. aureus confirming the antivirulence and antibiofilm activities. Favourably, no significant cytotoxicity of AMPT was observed on murine macrophage cell line. Taken altogether, these results suggest that AMPT could be considered an interesting lead compound in the search for treatment of MRSA infections. Graphical abstract: Image 1 Highlights: A thiazole compound (AMPT) was superior to vancomycin and teichoplanin against MRSA. AMPT exhibited antivirulence activity at subinhibitory concentrations. AMPT inhibited biofilm formation by MRSA, C. violaceum, and P. aeruginosa . Molecular docking revealed that AMPT binds AgrA and SarA in S. aureus . No cytotoxicity of AMPT was observed against murine macrophage cell line.